Series of 6 prints published in Bagatelle, Fantasio, Russie Illustrée, Le Sourire, Le Rire and Lustige Blätter - Pem,
Series of 6 prints published in Bagatelle, Fantasio, Russie Illustrée, Le Sourire, Le Rire and Lustige Blätter.